2015
DOI: 10.1016/j.oraloncology.2015.04.011
|View full text |Cite
|
Sign up to set email alerts
|

HPV16 antibodies as risk factors for oropharyngeal cancer and their association with tumor HPV and smoking status

Abstract: Backgound Antibodies (Abs) to the HPV16 proteome increase risk for HPV-associated OPC (HPVOPC). The goal of this study was to investigate the association of a panel of HPV16 Abs with risk for OPC as well as the association of these Abs with tumor HPV and smoking status among patients with OPC. Methods IgG Abs to the HPV16 antigens E1, E2, E4, E5, E6, E7, L1, L2 were quantified using a programmable ELISA assay. Sera were obtained from 258 OPC patients at diagnosis and 250 healthy controls. HPV16 tumor status … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
71
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
10

Relationship

5
5

Authors

Journals

citations
Cited by 51 publications
(79 citation statements)
references
References 36 publications
7
71
1
Order By: Relevance
“…In contrast, HPV16 antibodies are rare in healthy controls (<1%) [10]. At the time of diagnosis, HPV16 E6 antibodies are detected in most HPV-OPC cases [11,12]. Importantly, HPV16 E6 serology is not a good marker for predicting risk of cervical cancer (another HPV-related cancer) [13], increasing its potential for predicting HPV-OPC specifically when detected.…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, HPV16 antibodies are rare in healthy controls (<1%) [10]. At the time of diagnosis, HPV16 E6 antibodies are detected in most HPV-OPC cases [11,12]. Importantly, HPV16 E6 serology is not a good marker for predicting risk of cervical cancer (another HPV-related cancer) [13], increasing its potential for predicting HPV-OPC specifically when detected.…”
Section: Introductionmentioning
confidence: 99%
“…Of the 120 known types of HPV, the high-risk oncogenic HPV16 is the most frequent type, accounting for approximately 90-95% of HPV-positive OSCC [9,10]. Although HPV infection may be a major risk factor for OSCC [9,11 ], only a small fraction of individuals with a long period of high-risk HPV exposure develop OSCC, implying that host genetic factors may modify the association between HPV infection and risk of OSCC.…”
Section: Introductionmentioning
confidence: 99%
“…While HPV16 L1 seropositivity actually indicates that there has been prior HPV exposure, and this could and likely often occurred in other regions (e.g., anogenital sites, Etc), several recent studies have demonstrated that it is HPV16 E6/E7 that are associated with, or predictive of, HPV16-driven OPSCC 1921 . Therefore, serum anti-HPV16 L1 antibody seems to be only in a proportion of HPV16-associated OSCC in contrast to antibodies to the proteins E6 and E7, which cooperate in neoplastic transformation and clearly are linked to HPV-associated OSCC.…”
Section: Discussionmentioning
confidence: 99%